Influence of the Amount of Toothpaste on Cleaning Efficacy: An In Vitro Study - Sarembe, Sandra; Ufer, Carolin; Kiesow, Andreas; Limeback, Hardy; Meyer, Frederic; Fuhrmann, Ines; Enax, Joachim (European Journal of Dentistry, 2022)
Objectives The aim of this in vitro study was to test the influence of the amount of toothpaste on enamel cleaning efficacy.Materials and Methods The hydrated silica-based test toothpaste (radioactive dentin abrasion: 60.19 ± 1.35) contained all ingredients of a regular fluoride toothpaste. The cleaning efficacy of four different toothpaste amounts (1.00 g, 0.50 g [both “full length of brush”], 0.25 g [“pea-size”], and 0.125 g [“grain of rice-size”]) diluted in 1.00 mL water were each tested for different brushing times (10, 30, 60, 120, 180, and 300 seconds) using a standardized staining model on human molars with a brushing machine. Photographic documentation and colorimetric measurements were conducted, respectively, initially, after staining and after each brushing step. Colorimetric measurements were used to calculate the stain removal (in %).Statistical Analysis Results were analyzed by one-way analysis of variance with post hoc Tukey test and Levene's test for analysis of homogeneity of variance. The level of significance α was set at ≤ 0.05.Results The cleaning efficacy decreased significantly when using smaller toothpaste amounts. Stain removal after 120 seconds brushing time was: 77.4 ± 5.0% (1.00 g toothpaste), 75.7 ± 3.4% (0.50 g toothpaste), 54.1 ± 6.7% (0.25 g toothpaste), and 48.2 ± 7.1% (0.125 g toothpaste), respectively.Conclusion In this in vitro study the cleaning efficacy of a medium-abrasive, hydrated silica-based toothpaste was analyzed. Note that 1.00 g toothpaste showed for all brushing times a significantly higher cleaning efficacy than 0.25 g toothpaste and 0.125 g toothpaste.
Keywords: brushing machine; cleaning efficacy; enamel; teeth; toothpaste